Atrazine alters kisspeptin signaling and downstream neuroendocrine regulation following embryonic exposure in zebrafish - Sydney C. Stradtman; Umamaheswari Sathisaran; Benjamin K. Dierolf; Grace Sumner; Wagner Antonio Tamagno; Jennifer L. Freeman (Toxicology, 2026)

Correction: Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2026)

Structural and functional comparisons of salivary α-glucosidases from the mosquito vectors Aedes aegypti, Anopheles gambiae, and Culex quinquefasciatus - Adeline E. Williams; Apostolos G. Gittis; Karina Botello; Phillip Cruz; Ines Martin-Martin; Paola Carolina Valenzuela Leon; Benjamin Sumner; Brian Bonilla; Eric Calvo (Insect Biochemistry and Molecular Biology, 2024)

Molecular signatures of alternative reproductive strategies in a facultatively social hover wasp - Benjamin A. Taylor; Daisy Taylor; Alexandrina Bodrug‐Schepers; Francisco Câmara Ferreira; Nancy Stralis‐Pavese; Heinz Himmelbauer; Roderic Guigó; Max Reuter; Seirian Sumner (Molecular Ecology, 2024)
Social insect reproductives and non‐reproductives represent ideal models with which to understand the expression and regulation of alternative phenotypes. Most research in this area has focused on the developmental regulation of reproductive phenotypes in obligately social taxa such as honey bees, while relatively few studies have addressed the molecular correlates of reproductive differentiation in species in which the division of reproductive labour is established only in plastic dominance hierarchies. To address this knowledge gap, we generate the first genome for any stenogastrine wasp and analyse brain transcriptomic data for non‐reproductives and reproductives of the facultatively social species Liostenogaster flavolineata , a representative of one of the simplest forms of social living. By experimentally manipulating the reproductive ‘queues’ exhibited by social colonies of this species, we show that reproductive division of labour in this species is associated with transcriptomic signatures that are more subtle and variable than those observed in social taxa in which colony living has become obligate; that variation in gene expression among non‐reproductives reflects their investment into foraging effort more than their social rank; and that genes associated with reproductive division of labour overlap to some extent with those underlying division of labour in the separate polistine origin of wasp sociality but only explain a small portion of overall variation in this trait. These results indicate that broad patterns of within‐colony transcriptomic differentiation in this species are similar to those in Polistinae but offer little support for the existence of a strongly conserved ‘toolkit’ for sociality.

Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2023)
The relationships between flying Antarctic seabirds and their at-sea environments remain poorly understood, particularly outside of the breeding season. Improving our knowledge of how these marine predators use their habitat is a critical step towards conservation of these species. We tracked 27 adult Snow Petrels from two large breeding colonies in East Antarctica during the Austral winter (non-breeding period) – when they are primarily at sea away from their nesting sites. During this time, Snow Petrel habitat use was most associated with bathymetry (> 5000 m), low sea-surface height, relatively close distance to the southern boundary of the Antarctic Circumpolar Current, relatively close distance to the ice-edge, relatively high sea-ice concentration, and low sea-surface temperature. Individuals displayed various movement patterns: 20 birds occupied overlapping winter areas that ranged broadly (up to 2000 km) from their breeding sites. The remaining birds ventured far beyond their breeding sites – reaching a maximal distance from the colony of 5,268 km. One individual circumnavigated Antarctica. Daily activity patterns were related to day length, with peak activity occurring near dawn and dusk. Nocturnal activity increased from March until August/September. Key results reveal and depict Snow Petrel habitat maps for the non-breeding period in the East Antarctic region.

L-lactic and 2-ketoglutaric Acids, Odors from Human Skin, Govern Attraction and Landing in Host-Seeking Female Aedes aegypti Mosquitoes - Benjamin D. Sumner; Brogan Amos; Jan Bello; Ring T. Cardé (Journal of Insect Behavior, 2022)
Aedes aegypti , presented with a source of L-lactic and 2-ketoglutaric acid in a wind-tunnel bioassay, takeoff, fly upwind, and land on the odorant substrate at rates comparable to those exhibited by mosquitoes presented with a skin-odor stimulus. Addition of carbon dioxide decreased takeoff latency but was not required to elicit upwind flight nor landings. Ketoglutaric acid, a recently identified component of human skin odor, combined with lactic acid elicits the full repertoire of mosquito host-seeking behaviors.

Primacy of Human Odors Over Visual and Heat Cues in Inducing Landing in Female Aedes aegypti Mosquitoes - Benjamin D. Sumner; Ring T. Cardé (Journal of Insect Behavior, 2022)
Although human skin odor is thought to be the cue that anthropophilic mosquitoes use to discriminate us from other potential hosts, the precise details of how they use skin odor to find and land on a human is unclear. We found that Aedes aegypti land on a source of skin odor without a co-located visual cue. By collecting human odor on glass beads and using identical glass beads to visually conceal skin odor and heat cues, we were able to study mosquito landing on skin odor, heat, and visual cues separately. Landing is necessary for blood feeding which is a required behavior for the Aedes aegypti life cycle as well as the behavior responsible for the epidemiological impact of mosquitoes. Therefore, we consider it to be the diagnostic measure of the importance of a host cue. In two-choice tests, a skin odor source had the highest valence for landing, followed by a combination of heat and a visual cue, and finally heat and visual cues presented separately. We also measured the durations of the landings, though no significant differences were found.